Debt versus equity in development finance - Ulrich Lächler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
This essay aims to provide a theoretical foundation for two widely debated issues in development economics. The first concerns a current controversy associated with the external indebtedness of developing countries. The second relates to a longer standing debate over the effects of foreign capital inflows on domestic savings and growth.
Keywords: 330